New compact multiband inverted-L frequency reconfigurable antenna for cognitive radio applications - Abdullah Ali Jabber; Raad H. Thaher (Institute of Advanced Engineering and Science, 2020)
This paper presents, new compact and multiband frequency reconfigurable antenna for cognitive radio applications. A UWB sensing and reconfigurable communicating antennas are contained at the same substrate, where the UWB sensing antenna is an elliptical printed monopole antenna operates on frequency band from (2.65-22.112) GHz which can cover the UWB frequency band from 3.1 to 10.6 GHz, while the communicating antenna is an inverted-L frequency reconfigurable antenna operates on three bands of 1.49 GHz, 5.58 GHz, and 5.6 GHz under (S11 ≤ -10 dB) with a fractional bandwidth of 5.872%, 6.02%, and 6.05% respectively. The proposed antenna used to operate in two modes one for cognitive radio applications to cover WLAN applications at 5.5 GHz and 5.6 GHz and the second mode for wireless Ethernet, GPS synchronization, and Internet of Things that Matter (IoTtM) at 1.49 GHz. The frequency reconfigurability is obtained by using only a single RF switch (PIN diode) for changing the operating frequency. The antenna overall dimensions are 72 x 36 x 1.6 mm3 printed on an FR-4 epoxy substrate of 4.3 relative-permittivity, loss tangent tan (δ) = 0.002 and 50 Ω micro stripline feed. The obtained simulated gain is ranging from 1.35 to 4.132 dBi. The S11 and isolation (S12) between the two antennas are under -20 dB and -17 dB respectively at the resonant frequencies.